A manual of permanent plot procedures for tropical rainforests - Synnott, T (Commenwealth Forestry Institute, University of Oxford, 1979)
The purpose of this manual is to describe and recommend some of the most useful methods and techniques for permanent plots in indigenous, mixed tropical forests, for sample plots and for experimental and research plots. From accumulated experience and publications, many techniques developed in various countries and conditions have been collated to produce a standard recommended procedure with a number of options...